Some Properties of Hypergeometric Functions - Özergin, Emine (Eastern Mediterranean University (EMU), 2011)
ABSTRACT: This thesis consists of five chapters. The first chapter gives brief information about the thesis. In the second chapter, we give some preliminaries and auxilary results which we will use in thesis. In chapter three, the extension of beta function containing an extra parameter, which proved to be useful earlier, was used to extend Appell’s hypergeometric functions of two variables and extend Lauricella’s hypergeometric function of three variables. Furthermore, linear and bilinear generating relations for these extended hypergeometric functions are obtained by defining the extension of fractional derivative operator. Some properties of the extended fractional derivative operator are also presented. In chapter four, we consider generalizations of gamma, beta and hypergeometric functions. Some recurrence relations, transformation formulas, operation formulas and integral representations are obtained for these new generalizations. In chapter five, we present various families of generating functions for a class of polynomials in two variables. Furthermore, several general classes of bilinear, bilateral or mixed multilateral generating functions are obtained for these polynomials. Keywords: Generating functions, Hypergeometric function, Fractional derivative operator, Gamma function, Beta function. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tez beş bölümden oluşmuştur. Birinci bölümde tezin içeriği ile ilgili genel bilgiler verilmiştir. İkinci bölümde, tez boyunca kullanılacak olan temel bilgiler ve sonuçlar verilmiştir. Üçüncü bölümde, daha önceden kullanışlı olduğu ıspatlanmış olan ve ekstra bir parameter içeren genişletilmiş beta fonksiyonu kullanılarak, iki değişkenli genişletilmiş Appell hipergeometrik fonksiyonları ve üç değişkenli genişletilmiş Lauricella hipergeometrik fonksiyonları verilmiştir. Yine bu bölümde, yeni bir kesirli türev operatörü tanımlanarak, genişletilmiş hipergeometrik fonksiyonlar için lineer ve bilineer doğurucu fonksiyon bağıntıları elde edilmiştir. Genişletilmis¸ kesirli türev operatörünün bazı özellikleri de sunulmuştur. Dördüncü bölümde, genişletilmiş gamma, beta ve hipergeometrik fonksiyonlar ele alınmıştır. Bu yeni genelleşmeler için, bazı rekürans bağıntıları, dönüşüm formülleri ve integral gösterimler elde edilmiştir. Beşinci bölümde, iki değişkenli polinom sınıfı için bir çok doğurucu fonksiyon aileleri sunulmuştur. Yine bu bölümde, bu polinomlar için daha geniş bilineer, bilateral ve karışık multilateral doğurucu fonksiyon sınıfları elde edilmiştir. Anahtar Kelimeler: Doğurucu fonksiyon, Hipergeometrik fonksiyon, Kesirli türev operatörü, Gamma fonksiyonu, Beta fonksiyonu.
Doctor of Philosophy in Applied Mathematics and Computer Science. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2011. Supervisor: Assoc. Prof. Dr. Mehmet Ali Özarslan.
Keywords: Applied Mathematics and Computer Science; Generating Functions - Hypergeometric Function - Fractional Derivative Operator - Gamma Function - Beta Function